Época e técnica de poda verde de pessegueiro na obtenção dos frutos de qualidade - Dotto, Marcelo (2013)
One of the aspects that it should be considered in the fresh fruit market peach is the fruit quality. The visual aspect is the most important factor, it being the skin color relevant because it is associated with the fruit maturation and flavor. One of cultural techniques to improve the fruit quality is summer pruning, which has as main purpose to increase light penetration within the canopy tree and consequently it to promote the pigmentation, as well as improvements in the fruit flavor. However, this technique can to present results variable according to the time and manner in which it was realized. The aim of this work was evaluate the time and management type for summer pruning to obtain peach quality. The work was carried out at commercial orchard from Dois Vizinhos city, Paraná State, Brazil, in 2009/2010, 2010/2011 and 2011/2012 cycle. It was used Charme and Maciel peach varieties. The experimental design was completely randomized, in factorial 3. x 3 (summer pruning time x summer pruning management type), with 4 replications of two plants by plot. The summer pruning time were in the third, fourth and fifth week before harvest. First the cultural practices were realized removal vigorous vertical shoot inside and in the base of crown, break shoots and bad shoots position in the tree. The second in the bending shoots in the tree. The yield and physiology characteristics tree on orchard in 2010/2011 and 2011/2012 cycle and fruit physical-chemical- biochemistry variables were evaluated on Plant Physiology Laboratory. It was concluded that the summer pruning use in Charme and Maciel peach tree during four and five weeks before harvest, with the pruning and beding shoot increased the fruit quality.